Original paper Serological tests for syphilis performed in the Sexually Transmitted Diseases Diagnostic Laboratory in Poznań during 2000-2004 - Jakubowicz, Oliwia; Żaba, Ryszard; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Laboratory diagnostics of syphilis was introduced in 1906, when Wassermann and associates applied for the first time the complement fixation reaction, providing the background for dynamic development of diagnostic procedures. Aim : Comparison and analysis of positive serological reactions obtained during 2000-2004 in the Sexually Transmitted Diseases Diagnostic Laboratory of the Department of Dermatology, Medical University of Poznań. Material and methods : 40 067 results of serological tests for syphilis, which were performed in a group of 25 521 persons from the whole Wielkopolska Region, were analysed. The test tool was data analysis and comparison analysis. Results : Most of the serological tests for syphilis were performed in the first and the last year of the investigated period, i.e. in 2000 and 2004. From 2001 to 2003 the number of investigations was at a lower but similar level, with a slight tendency to decrease (the lowest level in 2003). The percentage of positive serological results in the investigated period was: 5.88% (2000), 6.83% (2001), 7.58% (2002), 8.86% (2003) and 6.36% (2004.). Conclusions : 1. Within the investigated period a significant difference in the number of serological tests for syphilis was recorded. 2. A significant difference, between investigated periods, was observed in the case of positive results for different serological tests. 3. Patients tended to have serological tests performed more frequently in the first quarter of the year.